POLA PENGASUHAN ANAK PADA TAMAN PENITIPAN ANAK ‘AISYIYAH WILAYAH RIAU - Sri Putri Hadayani; Indrawati " (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2014)
PARENTING CHILDREN ON CHILDREN’S DAYCARE ‘AISYIYAH IN RIAUThe activities of parent make the children can not be cared for maximality like other parent, it is caused the activities that spend many times them. In under five year, when the children need attention and love very much from their parent. The consequence of activities, their parent choose alternative way to cared for their children in order that the children can be cared for better when they do activity. The good of the research is to know how to parenting children on children’s daycare ‘Aisyiyah in Riau. The analyzing of data is done by explaining the data in frequency table form by describtive analize perfecbly by using percentage. The analyzing that is used in this research is all of data that is found in the field like primary and seconday data will be done category base on its kind and then it will be analized base on qualitative. The tecnique in this data is census. Census use all of people that is related. They are 5 nurse / nursemaid and the parent from the children that u cared for by their age up 3 year with total 15 people on children’s daycare ‘Aisyiyah in Riau. The result of this research is concluded that the parenting children that is applied at TPA ‘Aisyiyah in Riau is democratic parenting children, nurse / nursemaid always consult to parent in order that the parent know acveloping their children on TPA ‘Aisyiyah in Riau because location, that is close with their house or office.Keywords : Parenting, child, daycare